MISSION AND TASKS OF THE RESEARCH AND WORLD-CLASS UNIVERSITIES - Kuzmenko, Olga M. (Educological discourse, 2014)
It is analyzed the concepts of research and world-class universities; it is indentified their specific features, mission and tasks; it is emphasized the new role of the university in the knowledge triangle “education – science – business” at the expense of the strengthening of entrepreneurial culture and values.